Early Infectious Disease Outpatient Follow-up of Outpatient Parenteral Antimicrobial Therapy Patients Reduces 30-Day Readmission. (4th February 2019) - Saini, Ena; Ali, Mohammad; Du, Ping; Crook, Tonya; Zurlo, John
Abstract: We conducted a case-control study to examine the association between outpatient infectious disease (ID) follow-up and risk of 30-day readmission in 384 patients receiving outpatient parenteral antimicrobial therapy. ID outpatient follow-up within 2 weeks was associated with lower risk of all-cause 30-day readmission (adjusted odds ratio, 0.33; P = .0001).